2016
DOI: 10.1002/jrs.5049
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and identification of mixed pesticides' Raman signal and establishment of their prediction models

Abstract: A nondestructive and sensitive method is developed to determine mixed pesticides of acetamiprid, chlorpyrifos and carbendazim in apple samples by surface‐enhanced Raman spectroscopy (SERS). Self‐modeling mixture analysis (SMA) was used to identify and extract the Raman signals of each pesticide from the spectra of apples contaminated with mixed pesticides. Results indicate that the obtained SERS signal intensities of each pesticide in their mixture have no obvious difference to the signal intensities of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Surface-enhanced Raman spectroscopy (SERS) uses metals such as gold (Au) or silver (Ag) in colloidal form to enhance Raman signal intensity, greatly lowering detection limits. SERS has been widely used in food authentication research for detection of microorganisms and contaminants [ 35 , 36 , 37 , 38 , 39 , 40 ] and for detection of antibiotics in biomedical and pharmaceutical applications [ 41 , 42 ]. SERS has been applied to qualitatively detect antibiotics in aqueous solutions, demonstrating its potential for food safety applications [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman spectroscopy (SERS) uses metals such as gold (Au) or silver (Ag) in colloidal form to enhance Raman signal intensity, greatly lowering detection limits. SERS has been widely used in food authentication research for detection of microorganisms and contaminants [ 35 , 36 , 37 , 38 , 39 , 40 ] and for detection of antibiotics in biomedical and pharmaceutical applications [ 41 , 42 ]. SERS has been applied to qualitatively detect antibiotics in aqueous solutions, demonstrating its potential for food safety applications [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the bands of the acetamiprid (Mospilan 20 SP) were summarized in Table 2 where those described in previous works [27][28][29][30][31][32][33] are also presented for comparison. It is worth noting that the bands presented by Chen [27] relayed for the pure acetamiprid powder.…”
Section: Sers Of Mospilan 20 Spmentioning
confidence: 99%
“…Zhai et al studied the extraction and identification of the Raman spectral signatures of mixed pesticides and worked on the establishment of corresponding prediction models. They concluded that their method displays an ultrasensitive level of SERS performance for quantifying residual pesticides in apple samples without sample pretreatment, thereby showing great potential to serve as a useful means for monitoring mixtures of pesticide residues …”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%
“…They concluded that their method displays an ultrasensitive level of SERS performance for quantifying residual pesticides in apple samples without sample pretreatment, thereby showing great potential to serve as a useful means for monitoring mixtures of pesticide residues. [45] 9.4 | Tip-enhanced Raman spectroscopy Hoffmann et al used tip-enhanced Raman to map singlewalled carbon nanotube networks (SWCNTs) in conductive composite materials. Using TERS, the surface of a polymer-embedded conductive network of SWCNTs was mapped underneath a thin layer of pure polymer.…”
Section: Sers Substratesmentioning
confidence: 99%